2022
DOI: 10.1002/asi.24692
|View full text |Cite
|
Sign up to set email alerts
|

Personal information management burden: A framework for describing nonwork personal information management in the context of inequality

Abstract: This research reports on qualitative interviews with 31 participants who are Irish parents, identify as lesbian, gay, bisexual, queer (LGBQ), and who expressed difficulty in the process of obtaining birth certificates for their children. Our aim was to use personal information management (PIM) and personal digital archiving (PDA) as a lens to explore the invisible work that the Irish government requires of a sexual minority parent group to obtain "equal" treatment in the birth registration and birth certificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In Cushing and Kerrigan (2022), we found that while individuals maintain alternate personal information to construct their identity for themselves, they also maintain this information for their children, so their children are provided information that demonstrates that they are connected to family/an intended parent, even if the Irish government marginalizes them by not recognizing them as family in officially maintained documentation. Again, in this example, PIM maintenance is used to counter marginalization.…”
Section: Pim As Caring For Othersmentioning
confidence: 90%
See 4 more Smart Citations
“…In Cushing and Kerrigan (2022), we found that while individuals maintain alternate personal information to construct their identity for themselves, they also maintain this information for their children, so their children are provided information that demonstrates that they are connected to family/an intended parent, even if the Irish government marginalizes them by not recognizing them as family in officially maintained documentation. Again, in this example, PIM maintenance is used to counter marginalization.…”
Section: Pim As Caring For Othersmentioning
confidence: 90%
“…Exploring the reverse of this understanding, information that does not represent one's identity, also allows for viewing PIM as self-care. Cushing and Kerrigan (2022) explored instances of where official personal information (largely birth certificates and passports) did not represent the individual's identity as a parent, but which the individual had to maintain for the purpose of engaging with society. To counter this "does not represent me" view of the personal information, many participants maintained additional personal information that they thought did represent their identities as parents to "counter" the officially maintained documents by the state, and/or worked to change data collection systems, to allow for the recognition of multiple family structures.…”
Section: Pim As Self-carementioning
confidence: 99%
See 3 more Smart Citations